Seismological reference earth model in South China (SREM-SC): Upper mantle - Tang, Qingya; Sun, Weijia; Hu, Jiamin; Fu, Li-Yun (Frontiers in Earth Science, 2023)
This work is the mantle component of constructing the Seismological Reference Earth Model in South China (SREM-SC). Although there has been a wide range of research for imaging the upper mantle structures beneath South China, most of them focus on the large-scale features of the upper mantle, and the depth resolution is insufficient for existing surface wave tomography models to distinguish anomalies below 200 km. This study aims to develop a 3-D upper mantle Seismological Reference Earth Model in South China based on the prior tomography models. The shear wave velocity model comes from the analysis of several seismic surface wave tomography, supplemented by body wave tomography and the P-wave velocity model is constructed by the conversion from S-wave velocity. The radial anisotropy model is calculated from the SV-wave and SH-wave velocity. The Density model of the upper mantle is derived using the empirical relationship linking the density to the shear-wave velocity. The model is grid with 0.5° × 0.5° in latitude and longitude and 5 km interval in depth from 60 to 300 km. The mantle component of Seismological Reference Earth Model in South China is expected to provide a good representation of the upper mantle structures for further detailed studies. The mantle component of Seismological Reference Earth Model in South China provides new insights into upper mantle structures that should be meaningful to reveal the dynamic mechanism and tectonic evolution of South China.